Pravni vidiki zaposlovanja in odpuščanja starejših - Rataj, Primož (Delavci in delodajalci, 2016)
The contribution focuses on the legal position of persons older than 50 years of age concerning employment and dismissal of an employee in a labour relationship. At this age, the number of unemployed persons raises substantially. The author deals with the question whether one of the reasons for such situation could be also rights such as seniority bonus, the right to additional days of annual leave and special protection against dismissal according to labour legislation and collective agreements on the sectoral level. The author also outlines measures that are safeguarding the legal position of older persons as a correction of current situation.
Keywords: brezposelnost; odpoved; starejši ljudje; trg dela; zaposlovanje